(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Tourism is one of the biggest and fastest-growing sectors of the global economy. It is a primary platform for cross-cultural exchange and job creation. Every year millions of people travel to explore and visit different places, to learn about cultures, and to enjoy the wonders of nature. However, tourism also brings some challenges: environmental degradation, depletion of resources, harm to ecosystems and negative social effects within the culture (UNWTO, 2020). Issues such as these gave rise to the need for sustainable tourism in today’s tourism in recent years. In general, this article outlines a descriptive overview of sustainable tourism, and illustrates how responsible travel is reflected in how it affects the long-term tourism development. Sustainable travel emphasises protection of nature, the recognition of local culture, financial support to local communities and visitor satisfaction (UNEP, 2005). It includes the sustainable tourism aspect, environmental and social dimensions of tourism, revenue and potential benefits of tourism, the sustainability consequences of tourism and tourists. Sustainable tourism is tourism that serves people regardless of their present, and possible future state.